Demographic Situation and Demographic Security in the Regions of Russia’s Western Borderlands - Fedorov G.M. (Baltic Region, 2018)
In this study, I address the vast and complicated problem of population replacement in Russia’s border regions. Although both national and regional dedemographic indicators have improved in Russia in recent years, many issues relating to sub-replacement fertility, irrational migration, etc. remain unresolved. This lends an urgency to studying regional demographic security, namely, the problems of ensuring replacement fertility, regulating migrations, and overcoming a skewed age and sex structure. I provide a detailed definition of the notion of demographic security and a list of indicators for evaluating it. I stress typological differences in the demographic situation across Russia’s western borderlands to ensure a differentiated approach to providing regional demographic security. In this study, I use economic-statistical methods, a comparative analysis, and an empirical typology of regions based on the above indicators. In terms of theory, the findings obtained can contribute to a more detailed definition of demographic security and a better methodology of regional population studies. In practical terms, the study has relevance to the development of proposals for improving national and regional demographic policy and regional strategic planning given the identified typological differences.